An Analysis of Urban Livability for Children with Scenario Planning Approach (Case Study: District 3 of Tabriz) - Shahrivar Rostaei; Fariba Kouhi Gholghasem (تحقیقات کاربردی علوم جغرافیایی)
Today, in our country, cities have become the main place of work and life of the population and the amount of this population is increasing therefore, it is necessary to pay attention to the quality of life and the facilities needed by citizens and efforts to make cities livable. Increasing the city's livability can be the basis for Stability. It is important to pay attention to children because they are future citizens of society and they create the link between the past and the future generations. The present study, by using futures study  knowledge, identified key forces in the future of children's livabilityIn the first phase, using the Delphi method, we first identified some of the variables affecting the future status of urban living for children, Then we extracted 47 variables that were approved by experts and received the highest score. We divided these 47 variables into four environmental, physical, social, and economic groups. Then, using structural analysis method and creating a 47 * 47 matrix, these variables were compared using MICMAC software.  Finally, seven forces were extracted, which play key role in the future of children in the city. By using the Delphi method, has taken scenarios for these seven forces and 27 scenarios were written for forces and analyzed in the Scenario wizard software, and 3 strong scenarios, 7 believable scenarios and 309 poor scenarios were extracted. Finally, the results of the analyzes indicate that among the believable scenarios, 3 scenarios show favorable conditions, 3 scenarios, show continuation of the current process and 1 scenario shows completely critical situation. In addition, the results the survey of statistics and land per capita show that in the present situation, children's livability is not very desirable. Finally, solutions and suggestions were made to deal with critical scenarios.